MORPHOLOGICAL AND ANATOMICAL STUDY OF ZIZIPHORA PUSHKINII ADAMS. OF LAMINACEAE LINDL. FAMILY - F. K. Serebryanaya (Фармация и фармакология (Пятигорск))
Morphological and anatomical study of Ziziphora puschkinii Adams. was carried out. It resulted on the revelation of diagnostic signs of a stem, leafstalk and lamina structure. According to the present results, the nodal and caulifoliar morphology in Ziziphora may be helpful in systematic researches. Stomatal apparatus of diacytic type and big unicellular trichomes presence may be considered to be diagnostic signs of lamina epidermis. The data reseived may be uded in further systematic researches of Ziziphora L. genus.